THE IMPORTANCE OF AGRICULTURAL PRODUCTION FOR THE DEVELOPMENT OF AGROTOURISM ACTIVITIES IN PRAHOVA COUNTY, ROMANIA - Constantina Cati IACOB (IRIMIA) (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This paper aims to present the evolution of agriculture in Prahova County, in the period 2014-2018, analyzing in particular the production of cereals, fruits and vegetables without omitting animal husbandry and the production of milk and eggs. In order to highlight the main trends of agricultural production in Prahova County, the areas cultivated with cereals for grains, oil plants, potatoes, vegetables, as well as the areas occupied by orchards, vineyards and livestock were subjected to analysis. Grain cereals occupy an average of 95,502.4 hectares, being the largest area. This is followed by the average of oil plants with 27,156.6 hectares, followed by vegetables with an average of 4,230 hectares and potato cultivation with an average of 2,530.4 hectares. For the other crops analyzed, there were increases in maize, fodder, barley production and decreases in rye production. The analysis of fruit and vegetable production highlighted the fact that it belongs largely to private property, this being an asset for the development of slang tourism in Prahova County. Analyzing the milk production, a decreasing trend was found over the entire analyzed period.